Site-Seeing: Colorful Crusader Churches - Klawans, Jonathan (The Biblical archaeology review, 2023)
Seasoned visitors to Jerusalem surely know the Church of St. Anne, a pristinely preserved 12th-century Crusader church in the Romanesque style, near the beginning of the Via Dolorosa. Tradition associates the church’s grotto with the birthplace of Jesus’s mother, Mary, securing its importance for Christian pilgrims. Archaeology aficionados will value the ruins of the Pool […]